The centromere region of Arabidopsis thaliana chromosome 1 contains telomere-similar sequences. - Richards, E J (1991)
We describe the structure of an Arabidopsis thaliana genomic clone containing two classes of repetitive DNA elements derived from the centromere region of chromosome 1. One class is comprised of tandem arrays of a highly reiterated repeat containing degenerate telomere sequence motifs. Adjacent to these telomere-similar repeats we found a dispersed repetitive element reiterated approximately five times in the A. thaliana genome. The nucleotide sequence of the dispersed repeat is unusual, being extremely AT-rich and composed of numerous, overlapping repeat motifs.